Evidence of multiple point mutations in Theileria annulata cytochrome b gene incriminated in buparvaquone treatment failure - Chatanga, Elisha; Mosssad, Ehab; Abdo Abubaker, Hazem; Amin Alnour, Sondos; Katakura, Ken; Nakao, Ryo; Salim, Bashir (Acta tropica, 2019)
Drug resistance is one of the emerging and re-emerging epidemics affecting both veterinary and public health sectors. Buparvaquone provides the most satisfactory means in the treatment of bovine tropical theileriosis. However, recently there has been widespread reports of development of resistance of Theileria annulata to buparvaquone. To investigate the situation in Sudan where bovine tropical theileriosis is endemic, fifty blood samples from T. annulata-positive cattle. were used for DNA extraction, PCR and cytochrome b gene nucleotide sequencing. Analysis of the two buparvaquone binding site regions Q01 (130–148) and Q02 (244–266), revealed three non- synonymous mutations at codon 146; alanine (GCT) to threonine (ACT) within the Q01 region across all 50 isolates and the other mutation at codon 129; serine (AGC) to glycine (GGC) in 18 isolates which is very close to the Q01 binding site. However, we documented another mutation at position 227; valine (GTG) to methionine (ATG) close to the close to the Q02 binding site, in three isolates with mutation at codon 129. We concluded that this study has provided evidence of point mutations in the cytochrome b gene of T. annulata that might be associated with buparvaquone treatment failure in Sudan.